Molecular detection and antimicrobial resistance profiles of Extended-Spectrum Beta-Lactamase (ESBL) producing Escherichia coli in broiler chicken farms in Malaysia - Lemlem, Mulu; Aklilu, Erkihun; Mohammed, Maizan; Kamaruzzaman, Fadhilah; Zakaria, Zunita; Harun, Azian; Devan, Susmita Seenu (Public Library of Science, 2023)
Antimicrobial resistance is one of the major public health threats globally. This challenge has been aggravated with the overuse and misuse of antibiotics in food animals and humans. The present study aimed to investigate the prevalence of Extended-Spectrum β-lactamase (ESBL) genes in Escherichia coli (E. coli) isolated from broiler chickens in Kelantan, Malaysia. A total of 320 cloacal swabs were collected from farms in different districts of Kelantan and were analyzed using routine bacteriology, antimicrobial susceptibility test, and molecular techniques for further identification and characterization of ESBL encoding genes. Based on PCR detection for the E. coli species-specific Pho gene, 30.3% (97/320) of isolates were confirmed as E. coli, and 84.5% (82/97) of the isolates were positive for at least one ESBL gene. Majority of the isolates, 62.9% (61/97) were harboring blaCTX-M followed by 45.4% (44/97) of blaTEM genes, while 16.5% (16/97) of the isolates were positive for both mcr-1 and ESBL genes. Overall, 93.8% (90/97) of the E. coli were resistant to three or more antimicrobials; indicating that the isolates were multi-drug resistance. 90.7% of multiple antibiotic resistance (MAR) index value greater than 0.2, would also suggest the isolates were from high-risk sources of contamination. The MLST result shows that the isolates are widely diverse. Our findings provide insight into the alarmingly high distribution of antimicrobial resistant bacteria, mainly ESBL producing E. coli in apparently healthy chickens indicating the role of food animals in the emergence and spread of antimicrobial resistance, and the potential public health threats it may pose.